Comparative Kinetic Modelling and Performance Evaluation Of Immobilized Media Using Zeolite and Biokeramic In an Anaerobic Fixed-Bed Reactor Treating Dairy Sludge Waste - Pampang, Harun; Nogo Ole, Maria Assumpta; Ranggina, Dian; Moneteringtyas, Prisca Caesa (Reaktor, 2026)
This study evaluates the performance of anaerobic fixed-bed reactors using two different immobilization media, natural zeolite and porous bioceramic, for treating dairy sludge waste. Kinetic modeling was performed using Monod, Contois, and Moser models, implemented by MATLAB to determine substrate degradation (sCOD) and methane production rates. The results indicated that for the zeolite media, the Moser model provided the best fit R2 of 0.9287 and RMSE of 500.12 mg/L with an exponential constant (n) of 2.92, reflecting high microbial sensitivity and synergistic effects in the biofilm. In contrast, the bioceramic media showed higher statistical stability across all models, with the Monod and Moser models achieving an identical R2 of 0.9939. However, a significant functional discrepancy was observed, while bioceramic provided superior statistical fitting, it failed to facilitate effective methanogenesis, with methane concentrations remaining below 10%. Zeolite, despite a slightly lower statistical fit, achieved a peak methane concentration of 37.82% on day 6. This suggests that zeolite's cation exchange capacity effectively mitigates ammonia inhibition from protein-rich dairy sludge, a factor not captured by simplified empirical deterministic kinetic models. This research emphasizes that statistical stability in kinetic modeling did not inherently correlate with bio-energy recovery efficiency, affrim the importance of media selection.